2015
DOI: 10.4269/ajtmh.14-0403
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Group A Genotypes Detected Through Diarrheal Disease Surveillance in Haiti, 2012

Abstract: Abstract. Samples collected in 2012 through diarrheal disease surveillance in Haiti were tested for rotavirus by enzyme immunoassay and real time RT-PCR and positive samples were genotyped. The predominant genotypes were G1P[8] (29% prevalence) and G9P[8] (21%). The observed genotype prevalence was similar to that reported previously for other Caribbean countries.Group A rotavirus (RVA) is the primary cause of acute gastroenteritis in children 5 years of age worldwide. An estimated 453,000 children aged 5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…We demonstrated that a genotype shift from G3P [8] to G12P [8] occurred during the surveillance period. This genotype shift is consistent with findings from other US surveillance systems [39,60] as well as many countries [61][62][63][64][65] that found an increased incidence of genotype G12 during the 2012 RVA season; more specifically, the G12 lineage-III (allele A) associated with the P [8] genotype, although G12P [6] was found to be present at lower levels [18,19]. Phylogenetic analyses showed limited sequence (VP7 and VP4) variation within the common genotypes; most wild-type strains belonged to one lineage, with the exception of G1, G3 and G9 strains, which clustered within 2-3 lineages.…”
Section: Discussionsupporting
confidence: 91%
“…We demonstrated that a genotype shift from G3P [8] to G12P [8] occurred during the surveillance period. This genotype shift is consistent with findings from other US surveillance systems [39,60] as well as many countries [61][62][63][64][65] that found an increased incidence of genotype G12 during the 2012 RVA season; more specifically, the G12 lineage-III (allele A) associated with the P [8] genotype, although G12P [6] was found to be present at lower levels [18,19]. Phylogenetic analyses showed limited sequence (VP7 and VP4) variation within the common genotypes; most wild-type strains belonged to one lineage, with the exception of G1, G3 and G9 strains, which clustered within 2-3 lineages.…”
Section: Discussionsupporting
confidence: 91%
“…G12 RVA are considered emerging human RVA strains, and the lineage III G12 allele has spread worldwide rapidly [18, 19]. Strain G12P[8] was associated with a large outbreak of pediatric gastroenteritis in Rochester in 2007 (an outbreak detected through the NSVN) [13], and this genotype has been reported recently in Niger [20], Spain [21], Nicaragua [22], Haiti [23], and Australia [24]. It appears that G12P[8] strains now are established in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping was performed using reverse transcription PCR (RT-PCR) to determine the G and P genotypes. VP7 and VP4 genotyping RT-PCR was performed using a conventional multiplexed one-step amplification process with slight modifications ( Esona et al., 2015 ). In brief, the genotype G2 (G2-R4), G4 (G4-R2), and G9 (G9-R2) specific primers were replaced with updated versions: G2-R1 (TAT GTA GTC CAT YGT ATT AGT), G4-R1 (GAG CAT TCG MTA ATA MTG ATA ATA C), and G9-R3 (CAG AGT ATY YTT CCA TTC HGT ATC TCC) ( Esona et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In Haiti, data from the 2010–2012 RVA seasons showed that acute diarrhea accounted for 26% of hospitalizations in children under 5 years and 13% of hospital deaths ( Vinekar et al., 2015 ). Prior to vaccine introduction, G1P[8] was the predominant genotype circulating in Haiti, followed by G9P[8] ( Esona et al., 2015 ). In April 2014, the Ministry of Health introduced the monovalent vaccine, Rotarix, which is an attenuated human G1P[8] RVA strain ( Esona et al., 2015 ; Ward et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%